Balys Gajauskas correspondence - Gajauskas, Balys
Miniature letter (1982; Kuchino, Perm Oblast, U.S.S.R.) from Gajauskas, a Lithuanian political prisoner in a Soviet labor camp, to Max M. Kampelman, U.S. ambassador to the Conference on Security and Cooperation in Europe, Madrid, Spain (1980-1983), concerning human rights in Lithuania. Includes a typewritten translation in English. Also includes a letter (2000 March 16; Lithuania) from Gajauskas to Kampelman regarding the open letter of 1982 and the intervening years in Lithuania.
Lithuanian political activist and legislator and Soviet political prisoner.
Collection material in Lithuanian with English translation, in part.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Kampelman, Max M., -- 1920-2013 -- Correspondence; Human rights; Lithuania -- History -- 1945-1991.; Lithuania -- History -- 1991-; Legislators -- Lithuania; Political activists -- Lithuania; Political prisoners -- Soviet Union